Comparison of the sensory and physical quality of sand baking and conventionally grilled mackerel - Rosie Oktavia Puspita Rini; Agung Arif Gunawan; Tirta Mulyadi (AcTion: Aceh Nutrition Journal, 2025)
Food processing plays a critical role in maintaining food quality and safety. However, scientific information regarding the effectiveness of sand baking as an alternative cooking technique remains limited, particularly in the context of marine fish. This study aimed to compare the sensory and physical qualities of mackerel processed using sand baking and conventional grilling. This study was conducted from January to September 2025 using a laboratory experimental design. Twenty fish were divided into two treatment groups. Sensory evaluation was performed by three trained panelists using hedonic and hedonic quality tests to assess the samples. The physical analyses included measurements of the moisture content and texture. Data were compared using independent t-tests. The results showed that The sensory scores for both methods were categorized as good, with no significant differences in taste (p = 0.742), aroma (p = 0.423), texture (p = 0.423), or color (p = 0.423). The physical parameters were also comparable between the two treatments. In conclusion, sand baking can produce organoleptic and physical qualities equivalent to those achieved through conventional grilling. This technique has the potential to be an applicable and efficient alternative fish processing method for community use.